Reflection on the State and Perspectives of Didactics of Biology from the Perspective of the Faculty of Natural Sciences, CU in Bratislava - Ušáková, Katarína (Scientia in educatione, 2014)
The paper describes the original perspectives and impulses that initiated the development of didactics of biology in Slovakia, through the prism of research and educational activities performed at the Department of Didactics in Sciences, Psychology and Pedagogy, Faculty of Natural Sciences, Comenius University, Bratislava. Through a brief historical overview since the post-war period until present, the paper focuses on the personalities closely linked with the formation process of the didactics of biology. It further adverts to some common problems of natural sciences education in the context of the EU entry related socio-political changes and the EU driven educational reform convergence efforts. It further details the challenges of doctoral studies and the research in the field of didactics of biology, on the quality of which the level of teacher training of the future teachers of biology depends. The paper also concretizes the changes in the didactic curriculum that aim to improve the quality and usefulness of teachers’ preparation. At the end of the paper, the author points out the pervasive problems of didactics of biology, whose resolution would require greater degree of cooperation among all involved parts.